Pelatihan dan Pengembangan Branded Produk UMKM Desa Bedono Kluwung Kabupaten Purworejo - Jatmoko, Dwi; Purwanto, Joko; Nur Rohman, Fikri; Isti Arfiana, Shinta (Universitas Gajah Putih, Indonesia, 2023)
The role of students for society is needed. Students are agents of change for society in a better direction. Community Service Program (KKN) is a form of community service as a form of research in the field of science and technology to improve human resources in society. Group 27 Thematic Real Work Lecture (KKNT) Muhammadiyah University Purworejo for the 2022/2023 academic year was held in Bedono Kluwung Village, Kemiri District, Purworejo Regency. The KKNT activities were carried out from 5 January 2023 – 2 February 2023. Prior to the implementation of the KKNT, observations were made to determine the condition of the location. Observations were carried out using the following methods: (1) question and answer, (2) documentation, and (3) looking directly at the field. Knowing the potential and conditions in Bedono Kluwung Village, UMP KKN students organize work programs that can help and support the progress of Bedono Kluwung Village. The work programs are the Juvenile Delinquency Education Seminar at SMA Negeri 4 Purworejo, Public Health, namely Parenting, and UMKM in the village of Bedono Kluwung. In carrying out these programs, of course, we really need help from the people of Bedono Kluwung village. After we made observations, it turned out that many people already had small home-based businesses. Among them there is making salted eggs, making rengginang from cassava, making herbal medicine from spices, making birthday cakes and puddings and many others. In accordance with the theme of this year's KKNT